Association between prenatal care and low weight birth. A population level analysis (2022) - Silva-Vite, Carlos E. (2025)
Objective: To determine the association between the number of prenatal controls (PCN) and the prevalence of low birth weight (LBW) in individuals born during the post-COVID-19 era in Peru. Materials and Methods: This is a secondary study based on data from the 2022 National Demographic and Family Health Survey (ENDES). Low birth weight (LBW) was defined as a birth weight less than 2500 g. Sociodemographic and clinical variables were also evaluated to control for their influence and possible confounding effects on the study relationship. Results A prevalence of LBW of 4.1% was found. The adjusted analysis showed that for each completed CPN in pregnant women, the prevalence of LBW decreased by 12% (aPR: 0.88; 95% CI: 0.80-0.96). A significant association was also found between LBW and factors such as iron supplementation (aPR: 7.42; 95% CI: 1.05-52.32) and having Spanish as the mother tongue (aPR: 0.47; 95% CI: 0.27-0.83). Conclusion: A statistically significant relationship was found between the number of prenatal checkups and the prevalence of low birth weight in Peruvian children surveyed by the ENDES in 2022. These results are similar to those found in studies prior to 2020.